2021
DOI: 10.1039/d0nh00559b
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric polymer-based artificial synapse for neuromorphic computing

Abstract: Recently, various efforts have been made to implement synaptic characteristics with a ferroelectric field-effect transistor (FeFET), but in-depth physical analyses have not been reported thus far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 45 publications
1
73
0
Order By: Relevance
“…In an ideal synaptic device, both NL and AR factors are zero. [ 48–51 ] As identified in Figure 6a, the NL values of the UVO‐treated WEST (w/UVO) are 0.32 in LTP and −0.55 in LTD, respectively, which are very close to zero compared to those of the untreated WEST 5.91 in LTP and −6.11 in LTD, respectively. In addition, the calculated AR of the UVO‐treated WEST is 0.089, which is 1/10 of that of untreated WEST (0.83).…”
Section: Resultsmentioning
confidence: 74%
“…In an ideal synaptic device, both NL and AR factors are zero. [ 48–51 ] As identified in Figure 6a, the NL values of the UVO‐treated WEST (w/UVO) are 0.32 in LTP and −0.55 in LTD, respectively, which are very close to zero compared to those of the untreated WEST 5.91 in LTP and −6.11 in LTD, respectively. In addition, the calculated AR of the UVO‐treated WEST is 0.089, which is 1/10 of that of untreated WEST (0.83).…”
Section: Resultsmentioning
confidence: 74%
“…Besides, the polarization of the ferroelectric layer will be even stronger via voltage pulse modulation, leading to a much more significant channel conductance change [81]. So far, 2D channel materials have been intensively exploited to build high-performance FeFET to emulate synaptic behaviors by combining with either the conventional ferroelectric gate stack (such as Zr-doped HfO 2 , P(VDF-TrFE), PZT) or the 2D ferroelectrics (such as CIPS and α-In 2 Se 3 ) [81][82][83][84][85][86][87][88][89]. In the following session, we will further review the latest reported three-terminal ferroelectric memory devices based on 2D materials.…”
Section: Three-terminal Devicesmentioning
confidence: 99%
“…Besides, the device could still exhibit synaptic behavior after 10 7 cycles of stimulation, though degradation is observed in depression owing to the increasing negative coercive voltage (figure 8(c)). Following the discovery of high-performance P(VDF-TrFE)/MoS 2 -based single synaptic transistor, Kim et al further systematically studied the influence of formation temperature of P(VDF-TrFE) and metal contacts on the training and recognition tasks via MNIST datasets [81]. Specifically, the dataset included 10 categories of items and was built up by training/test images, in which each image has 784 pixels.…”
Section: P(vdf-trfe) and 2d Materials-based Three-terminal Devicesmentioning
confidence: 99%
“…Recent reports showed the promising behavior of polymer FE P(VDF‐TrFE)‐based electronic synapses and neurons, operating at nanosecond timescales. [ 63–67 ] However, before converting them to a technologically matured solution, more research needs to be done, especially at the memory array level. For the doped‐HfO 2 based FE memories, majority of reported materials and devices employed a high‐temperature rapid thermal annealing to attain the noncentrosymmetric orthorhombic polar phase.…”
Section: Fe Memoriesmentioning
confidence: 99%
“…However, instead of an identical pulse scheme, an incremental pulse scheme is used to achieve this accuracy. Kim et al [ 67 ] studied the influence of the FE properties and contact barrier heights in the FeFET synapses based on P(VDF‐TrFE) on the training and recognition performance of a multilayer perceptron (MLP)‐based neural network ( Figure ). Two different datasets from the MNIST database, i.e., the fashion and handwritten digits, were used for the training and inference tasks.…”
Section: Application In Neuromorphic Architecturesmentioning
confidence: 99%